Ilustrasi Sebagai Media Representasi Self-Cherishing Dan Self-Acceptance Dalam Perspektif Visual Studi Fenomenologis - Wardani, Lely Surya; Hendrawan, Faldi (Jurnal Desain Komunikasi Visual Asia, 2025)
Illustration as a medium that can be used to understand and spread self-love because it can be used to convey messages visually and emotionally. This study examines 2 components of self-love, namely self-cherishing and self-acceptance. The problems faced by students are related to the pressure to achieve, adapt to new environments, and demands to build self-identity often cause stress that has an impact on psychology. This research aims to explore how illustration can be an effective medium to represent 2 components of self-love from a visual perspective through a phenomenological approach. In addition, it is also to find out how many students are able to appreciate, accept, and appreciate as a form of loving themselves through visual works, which reflect the essence of emotion and meaning behind the visual experience. The results of this research are that students who draw themselves can be stated to have a higher understanding of the aspect of self-love than those who draw others. Through the observed phenomena, students' awareness in understanding the components of self-love can be said to be good visually through the results of the illustrations. However, in everyday life, the level of students' self-love can still be said to be sufficient to tend to be lacking in accepting, appreciating, respecting and considering themselves more important than others.